The chemical treatment of cooling water - McCoy, James W. (Chemical Pub. Co., 1983)
This standard reference serves the industrial community as an authoritative source on cooling water problems. Analysis includes the problems of corrosion measurement and control; cooling water additives; advances in treatment chemicals and chemical cleaning, maong other topics.